Pengembangan STAIN: antara Tantangan dan Peluang di Indonesia - moh roqib (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
If we notice Undang-undang Republik Indonesia Nomor 14 Tahun 2005 about Teacher and Lecturer, and Peraturan PemerintahÂ Republik Indonesia Nomor 19 Tahun 2005 about National Standard of education, we realize that itâ€™s a chance for PTAIN (State Islamic Higher Education) to strengthen its position, politically or socially. Here, role of alumni, academician, and Department of Religion officer that in charge of education, is to build plan and concrete action using all potential and involved every institution related. With this fine planning and cooperation of every institution, solution about Islamic education will be found.